PENGARUH MASSAGE ABDOMEN TERHADAP KONSTIPASI PADA PASIEN YANG TERPASANG VENTILASI MEKANIK DI RUANG ICU - Sari, Ni Made Dwi Purnama; Wulandari, Made Ririn Sri; Triana, Komang Yogi (Universitas Kusuma Husada Surakarta, 2021)
Constipation is most common occurred in mechanically ventilated patients. Constipation that occurs in mechanically ventilated patients is often the cause of failed weaning. Constipation in a mechanically ventilated patient can be observed using the constipation scoring system. Nurses have an important role in overcoming constipation in patients who are mechanically ventilated during treatment. One of the non-pharmacological therapies that nurses can do to treat constipation is abdomen massage. This study aimed to determine the effect of abdomen massage on constipation experienced by patients with mechanical ventilation in the ICU Ward of X Hospital Denpasar. This study used a quasi-experimental design with a posttest only control group approach. The sampling method was purposive sampling, with one intervention and control group, each group consisted of 10 members. The data were analyzed using Shapiro Wilk test to determine the distribution of the data that had been obtained and using the Independent Sample T-Test to compare the posttest results of the intervention and control group. There was an effect of abdomen massage on constipation experienced by patients with mechanical ventilation with a Sig. (2-tailed) value of 0.00 with r value of 0.05, meaning that Sig. (2-tailed) <0.05. Therefore it can be concluded that there was an effect of abdomen massage on constipation experienced by patients with mechanical ventilation in the ICU Ward of X Hospital Denpasar. It is expected that in the treatment of patients with mechanical ventilation, abdomen massage can be applied to overcome constipation so that the weaning process can run smoothly.